2021
DOI: 10.1007/s12015-021-10235-6
|View full text |Cite
|
Sign up to set email alerts
|

NFĸB Targeting in Bone Marrow Mesenchymal Stem Cell-Mediated Support of Age-Linked Hematological Malignancies

Abstract: Mesenchymal stem cells (MSCs) can become dysfunctional in patients with hematological disorders. An unanswered question is whether age-linked disruption of the bone marrow (BM) microenvironment is secondary to hematological dysfunction or vice versa. We therefore studied MSC function in patients with different hematological disorders and found decreased MHC-II except from one sample with acute myeloid leukemia (AML). The patients' MSCs were able to exert veto properties except for AML MSCs. While the expressio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…We do not propose to change the standard of care, but to monitor circulating BCCs as a functional indicator for targeted treatment to prolong BC remission. Studies with hematological cancer showed that induced differentiation of leukemia stem cells with bortezomib could induce chemosensitivity [ 61 ]. Despite the limited number of analyzed BCCs in blood (Table 1 ), the evidence showed intriguing information that similar analyses could be used in expanded studies to guide how BC patients are treated.…”
Section: Discussionmentioning
confidence: 99%
“…We do not propose to change the standard of care, but to monitor circulating BCCs as a functional indicator for targeted treatment to prolong BC remission. Studies with hematological cancer showed that induced differentiation of leukemia stem cells with bortezomib could induce chemosensitivity [ 61 ]. Despite the limited number of analyzed BCCs in blood (Table 1 ), the evidence showed intriguing information that similar analyses could be used in expanded studies to guide how BC patients are treated.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, EVs have been studied as cargo of various oligonucleotides of natural and synthetic origin like Paclitaxel, Doxorubicin a nd phytochemicals (64). Another mechanism exploited by MPN-MSCs could be an exaggerated activation of the proinflammatory NF-kB pathway, leading to cytokine release, and proliferation and maintenance of the mutated HSCs and myeloid and lymphoid precursors (65,66).…”
Section: A Role For Mscs In Mpnmentioning
confidence: 99%
“…Moreover, based on the reported hyperactive NF-kB signalling in MPN-MSCs, this pathway could serve as a target in a combined therapeutic approach against haematological malignancies, using for example a NF-kB inhibitor such as Bortezomib or Carfilzomib (66).…”
Section: Therapeutic Implicationsmentioning
confidence: 99%
“…In the age-remodelled BM, MSCs show alteration that reduced production of niche factors that support HSC maintenance, increased adipogenesis and reduced osteogenesis which contribute to a myeloid skewed phenotype of HSCs in aged marrow 17 . Several studies show that microenvironments composed of aged MSCs associate with leukemia development 18 . However, whether cell intrinsic ageing of MSCs affects their function to support normal and pathogenic haematopoiesis, or as a source of tissue regeneration, remains unknown.…”
Section: Introductionmentioning
confidence: 99%